Antioxidant and antihypertensive effects of garlic protein and its hydrolysates and the related mechanism. Issue 2 (26th December 2019) - Gao, Xudong; Xue, Zihan; Ma, Qiqi; Guo, Qingwen; Xing, Lisha; Santhanam, Ramesh Kumar; Zhang, Min; Chen, Haixia
Abstract: Garlic protein (GP) was enzymatically hydrolyzed using pepsin and trypsin followed by the evaluation of antioxidant and angiotensin‐converting enzyme (ACE) inhibitory activities of GP and its hydrolysates. The antihypertensive effects of GP and its hydrolysates were determined in vivo. The results showed that GP and its hydrolysates namely GPH‐P (pepsin) and GPH‐T (trypsin) possessed appreciable antioxidant and ACE inhibitory activities. The ACE inhibitory activity of GP, GPH‐T, and GPH‐P was in consistent with their antioxidant activities. GP and its hydrolysates offered significant protective effects against H2 O2 ‐induced oxidative damage ( p < .05). In addition, the administration of GP, GPH‐T, and GPH‐P reduced the blood pressure in hypertensive rats. The mechanism might be to reduce blood pressure by inhibiting the activity of ACE, reducing the formation of ACEII, and protecting the activity of bradykinin. This study suggested that GP might be utilized as a promising functional food as antioxidant and antihypertensive agents. Practical applications: Garlic ( Allium sativum L.) is one of the oldest cultivated plants that belongs to the Liliaceae family and it has been used in cooking and medicinal applications. Large quantities of garlic residuals were produced with the development of the garlic essential oil industry. These residuals are highly rich in proteins and they can be used for the preparation of protein hydrolysates. Generally, hydrolysates are considered as a promising food supplement due to the enrichment of amino acids present in it. In this study, garlic proteins (GPs) and its hydrolysates retain effective antioxidant effects. They were found to reduce the blood pressure and prevent oxidative stress induced by H2 O2 . The information from this study could be used to develop a new nutritional supplement from GP and its hydrolysates to treat hypertension as well as prevent oxidative damage. Abstract : The hydrolysates by pepsin and trypsin enhanced antioxidant capacity and ACE inhibitory capacity. Garlic protein and its hydrolysates have protective effects on H2 O2 ‐induced oxidative damage of L02 cells. Garlic protein could be a potential suitable nutritional supplement in the food industry.